Peran Guru IPS Dalam Menanamkan Karakter Disiplin Dan Tanggung Jawab Siswa MTsN 1 Lamongan - Iif Aisyah; Warsono Warsono; Wisnu Wisnu (EduInovasi: Journal of Basic Educational Studies, 2023)
This study aims to (1) identify and describe the role of social studies teachers in implementing discipline character education and student responsibility at MtsN 1 Lamongan, and (2) identify and explain the obstacles experienced by teachers in implementing student discipline and responsibility character education. at MtsN Lamongan. The method used is descriptive qualitative with teacher and student informants with interview, observation, and documentation techniques. The data analysis technique used the Milles and Habermas technique which started from data collection, data reduction, data study, and drawing conclusions. The results of the study revealed that (1) the teacher's role in instilling the character of discipline and responsibility of the students of MtsN 1 Lamongan is by example, enforcement, and habituation. (2) supporting and inhibiting factors come from the school environment, family and community. while (3) the solution is in the form of cooperation between the school and parents and the active role of the teacher.